Plants vs. zombies. 12, Dino-might - Tobin, Paul, 1965- (Plants vs. Zombies, 2019)
"When Zomboss sets his sights on destroying the yards in town, it is up to the daring duo, along with Crazy Dave and his band of plants, to thwart his plans and claim victory once again!"--